2020
DOI: 10.1016/j.jacr.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Chronic Foot Pain

Abstract: Chronic foot pain is a frequent clinical complaint, which can significantly impact the quality of live in some individuals. These guidelines define best practices with regards to requisition of imaging studies based on specific clinical scenarios, which have been grouped into different variants. Each variant is accompanied by a brief description of the usefulness, advantages, and limitations of different imaging modalities. The present narrative is the result of an exhaustive assessment of the available litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The American College of Radiology guidelines state that plain radiography, although not sensitive, is initially indicated for plantar fasciitis (Expert Panel on Musculoskeletal Imaging, et al., 2020). In our study, standard radiographs showed plantar calcaneal spurs in 12 patients (30%) and 20 heels (25%).…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Radiology guidelines state that plain radiography, although not sensitive, is initially indicated for plantar fasciitis (Expert Panel on Musculoskeletal Imaging, et al., 2020). In our study, standard radiographs showed plantar calcaneal spurs in 12 patients (30%) and 20 heels (25%).…”
Section: Discussionmentioning
confidence: 99%
“…MRI features associated with Plantar fasciitis include thickening and inflammation in the plantar aponeurosis, adjacent soft-tissue edema, reactive calcaneal marrow edema, and any evidence of rupture of the fascia if present. MRI has been given a score of 9 on the American College of Radiology appropriateness criteria [76,77]. Although, highly sensitive, MRI has limited specificity for the detection of the exact pain generator in the foot, especially in cases where multiple pathologies coexist.…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…We reviewed relevant recommendations related to the 25 clinical/diagnostic scenarios previously published by radiology and specialty societies, including: the Canadian Association of Radiologists, 9 the American Academy of Orthopaedic Surgeons, 10,11 the American College of Physicians (ACP), 12 the American College of Radiology (ACR), [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] the Brazilian Society of Rheumatology, 31 the combined guideline by the European Association of Nuclear Medicine, the European Bone and Joint Infection Society, and the European Society of Radiology, [32][33][34] the European League Against Rheumatism (EULAR), 35,36 the European Society of Musculoskeletal Radiology, 37 the European Society for Medical Oncology, 38 39 the International Consensus on Orthopedic Infections, 40 the International Hip-related Pain Research Network, 41 the Lisbon Agreement, [42][43][44] the National Institute for Health and Care Excellence, 45-52 the Paget's Association, 53 the Royal College of Radiologists (RCR), 54 the Society for Vascular Surgery in collaboration with the American Podiatric Medical Association and the Society for Vascular Medicine, 55 the Spanish Society of Rheumatology, …”
Section: Systematic Scoping Reviewmentioning
confidence: 99%